Efficacy of artemether .. lumefantrine and artesunate-amodiaquine for treating uncomplicated falciparum malaria in children - Tri Faranita; Ayodhia Pitaloka Pasaribu; Muhammad Ali; Munar Lubis; Syahril Pasaribu (Indonesian Pediatric Society Publishing House, 2012)
Background Artesunate􀁁amodiaquine (ASAQ) has been used as a firsdine treatment for uncomplicated faldparum malaria in Indonesia since 2004. Its efficacy depends on amodiaquine resistance of the infecting parasites. Artemether􀁁lumefantrine (AL) has been shown to be highly efficacious in treating uncomplicated faldparum malaria in several countries. However, there have been few studies on these anti􀁁malarial medications in Indonesia. Objective To compare the efficacy of AL to ASAQ for treating uncomplicated faldparum malaria in children. Methods An open, randomized, controlled trial was conducted in school􀁁aged children in the Mandailing Natal Regency, North Sumatera Province, Indonesia, from October to December 2010. A total of 280 pediatric, uncomplicated falciparum malaria patients were randomly assigned to receive either AL or ASAQ for 3 days. Participants were followed􀁁up on days 1,2,3,7, 14, 28 and 42 following the first medication dose. The outcomes noted were adequate clinical and parasitological response (ACPR), parasite reduction, parasite clearance time, fever clearance time and adverse events. Analysis was based on intention􀁁to􀁁treat. Results In this study, ACPRs on day 42 were 86.4% and 90.7% for the ASAQ and AL groups, respectively (p􀁂O.260). On days 7 and 14, the AL group had higher cure rates than that of the ASAQ group (P<O.OS). Early treatment failure, late treatment failure and parasitological failure for both groups were similar. We also found faster parasite clearance time and higher parasite reduction in the AL group than in the ASAQ group. However, fever clearance time was shorter in the ASAQ group. The incidence of adverse events such as nausea, vomiting, malaise, and pruritus were similar between the two groups (P􀁂O.441). Conclusion AL had higher efficacy than ASAQ for the treatment  of uncomplicated falciparum malaria in children. [Paediatr rndones. 2012;52:260-6].